Autoimmune gastritis diagnosed due to recurrent gastric neuroendocrine tumor: a case report - Yang, Qunying; Jin, XiangHong; Lv, Xiangyin; Hu, JianWen (Frontiers in Medicine, 2025)
As digestive endoscopy becomes more prevalent, an increasing number of autoimmune gastritis (AIG) cases have been diagnosed, which has contributed to a growing body of research on AIG. We report the case of a patient with AIG who was diagnosed due to receiving endoscopic surgery after discovering a gastric neuroendocrine tumor (GNET) during gastroscopy twice within 3 years. The patient was admitted to our hospital for endoscopic submucosal dissection (ESD) due to GNET recurrence discovered during gastroscopy. The patient had previously undergone ESD due to a GNET discovered during gastroscopy 3 years ago. Recent repeat gastroscopy revealed severe mucosal atrophy in the gastric body and fundus, an ulcer in the gastric antral, and two mucosal bulges in the gastric body. Pathology indicated Grade 2 (G2)-GNET, and ESD was performed again. The patient also had iron deficiency anemia and thyroid dysfunction, elevated gastrin, and decreased pepsinogen I (PG I) and PG I/II. Hence, AIG was diagnosed. Recurrent GNET cases, especially those with concurrent anemia and abnormal thyroid function, may experience AIG. In addition to symptomatic treatment, the clinician must evaluate the patient's overall condition.